Combined fMRI Region- and Network-Analysis Reveal New Insights of Top-Down Modulation of Bottom-Up Processes in Auditory Laterality - Kazimierczak, Katarzyna; Craven, Alexander R.; Ersland, Lars; Specht, Karsten; Dumitru, Magda L.; Sandøy, Lydia B.; Hugdahl, Kenneth (Frontiers in Behavioral Neuroscience, 2022)
Dichotic listening, and the right-ear advantage (REA), has been a standard method of investigating auditory laterality ever since it was first introduced into neuropsychology in the early 1960s. Beginning in the 1980s, authors reported that it was possible to modulate the bottom-up driven perceptual REA by instructing subjects to selectively attend to and report only from the right or left ear. In the present study we investigated neuronal correlates of both the bottom-up and top-down modulation of the REA through two fMRI analysis approaches: a traditional region approach, and a cortical network connectivity approach. BOLD fMRI data were acquired while subjects performed the standard forced-attention paradigm. We asked two questions, could the behavioral REA be replicated in unique brain markers, and secondly if the profound instruction-induced modulation of the REA found in behavioral data would correspond to a similar modulation of brain activation, both region-, and network-specific modulations. The subjects were 70 healthy adult right-handers, about half males and half females. fMRI data were acquired in a 3T MR scanner, and the behavioral results replicated previous findings with a REA in the non-forced (NF) and forced-right (FR) conditions, and a tendency for a LEA in the FL condition. The fMRI data showed unique activations in the speech perception areas of the left temporal lobe when directly contrasted with activations in homologous right side. However, there were no remaining unique activations when the FR and FL conditions were contrasted against each other, and with the NF condition, using a conservative significance thresholding. The absence of task-specfic activations in the attention-instruction conditions is conceptualized within an EMN-network frame of reference, where the EMN is seen as a task non-specific cortical network which is upregulated whenever the task demands exceeds a certain threshold irrespective of the specifics and demands of the task.